Summary – Good Practices - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The chapter formulates short concluding thoughts on the importance of communication in connection with the enforcement of children’s rights. The importance of more effective contact with children and communication competencies has increased especially as a result of the recent research results, the specific characteristics of the information society and the recognition of the impressions that children have during encounters with the authorities. New concepts such as trauma-focused justice have emerged. These expectations formulated at the international level and the recommendations of organizations dealing with children clearly make it necessary to expand the knowledge of professionals in the field and to strengthen their practical skills.Keywords: role of communication, youth justice, children rights, good practices, neurodivergence, traumainformedjustice